Development and psychometric evaluation of a reflection on clinical practice questionnaire for nursing students - Mostafa Bijani; Fateme Mohammadi; Fariba Haghani; Nikoo Yamani; Shahnaz Karimi (BMC, 2021)
Abstract Background Reflection on clinical practice is the core of education for nursing students. Evaluating reflection on clinical experiences requires a tool which accurately measures reflection skills. The present study aims to develop and test the psychometric properties of a tool for measuring nursing students' reflection on clinical practice. Methods Based on a mix-method exploratory approach, the study was carried out in two stages: in the first stage (the qualitative phase), the concept of reflection on clinical practice was established. In the second stage (the quantitative phase), the psychometric properties of the developed scale were evaluated. Results Based on the results of the exploratory factor analysis and the verification process, the final version of the scale came to consist of 36 items and 6 dimensions. The dimensions were: professional competence, internal sources of motivation, challenging situational clinical setting, dynamic organizational atmosphere, reflection-based self-management, and dynamic professional growth. Overall, 6 factors accounted for 62.79% of the variances. The factor loadings of the items ranged between 0.62 and 0.94, all of which were significant. The total intraclass correlation (ICC) of the scale was found to be 0.94. Also, evaluation of the reliability of the scale as measured through internal homogeneity yielded a total Cronbach's alpha of 0.90. Conclusion The findings show that the developed scale for evaluation of nursing students' reflection on clinical practice possesses satisfactory validity and reliability, and nursing professors can use this instrument to assess students' reflection skills.